The development of Islamic banking laws in Malaysia: an overview - Ruzian Markom; Norilawati Ismail (Fakulti Undang - Undang, 2009)

(untitled)
Malaysia is well regarded by the international community as one of the leading Islamic financial centers. This was evidenced by the launching of an initiative by the Malaysian Government known as the Malaysian International Islamic Financial Centre (MIFC) on 14 August 2006. Behind this successful achievement, the emergence of Islamic banking in Malaysia stemmed from the establishment of the first full-fledged Islamic bank offering Islamic products and services in 1983 known as Bank Islam Malaysia Berhad (BIMB) under the Islamic Bank Act 1983. This article examined the development of Islamic banking and financial laws in Malaysia. Firstly, the background of Islamic banking and finance is addressed. Secondly, the development of the industry is described from its infancy days until its recent achievement to become an Islamic financial hub. The next section dwells upon the issues relating to the current legislative jurisdiction and Shariah supervision on the matters. Finally, while the study illustrates that the finance industry is evolving progressively, further efforts and reformation are needed for the country to sustain as ‘Malaysia International Islamic Financial Centre’